Chlorella sorokiniana HS1, a novel freshwater green algal strain, grows and hyperaccumulates lipid droplets in seawater salinity. (February 2016) - Kim, Byung-Hyuk; Ramanan, Rishiram; Kang, Zion; Cho, Dae-Hyun; Oh, Hee-Mock; Kim, Hee-Sik
Abstract: Salinity is a major abiotic stress for terrestrial plants and freshwater microalgae alike. The most notable physiological response of microalgae like Dunaliella to salinity stress is reduced photosynthesis and production of carotenoids. Here, we report isolation and characterization of a novel freshwater microalgal strain, Chlorella sorokiniana HS1, which grows and hyperaccumulates lipid droplets (LD) in hypersaline conditions greater than seawater salinity. Other freshwater Chlorella strains tested neither grew nor possessed high LD levels in high salt concentration. C. sorokiniana HS1 displayed increase in cell size (200%) and LD, resulting in increased biomass and lipid productivity, respectively, with altered but favourable fatty acid methyl ester composition under salinity stress. Experimental analyses reveal definitive shift from proteins and starch to LD synthesis as well as chlorophyll degradation, response analogous to nitrogen starvation. Acute salt stress (<6 h) in seawater salinity or above resulted in instant accumulation of LD. C. sorokiniana HS1 allows for two phase cultivation, growth phase in freshwater and stress induction phase in seawater for biodiesel production. This strain would therefore significantly reduce costs and production constraints associated with stress induction. Highlights: A halo-tolerant Chlorella sorokiniana HS1 strain was isolated from swine wastewater. Grows and hyperaccumulates lipid droplets (LD) in hypersaline conditions (0–60 g L −1 ). Salt concentration dependent induction of LD accumulation. Results reveal increased cell size, and protein, starch and chlorophyll degradation. Desirable lipid content and FAME profile make it ideal for two-phase production.